(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The persistence of the marital rape exception in Indian criminal law constitutes not merely a legislative lacuna but a structural condition that reproduces gendered harm across multiple dimensions of well-being. This paper undertakes a doctrinal analysis of the legal framework governing marital rape in India — from the Indian Penal Code, 1860 to the Bharatiya Nyaya Sanhita, 2023 — and examines its intersection with the nutritional deprivation of women and children. Drawing on constitutional jurisprudence, feminist legal theory, international human rights instruments, and peer-reviewed empirical research, the paper argues that the non-criminalisation of marital rape violates the fundamental rights of women and children, including the constitutionally recognised right to nutritious food under Article 21 of the Constitution of India. The analysis establishes that legal reform criminalising marital rape is not merely a gender justice imperative but a necessary public health intervention to safeguard the nutritional rights of women and children. The paper proceeds through a critical engagement with judicial decisions, statutory provisions, treaty obligations, and empirical findings to demonstrate the normative and material connections between sexual coercion within marriage and nutritional deprivation as a justiciable constitutional harm.